Formation of N-nitrosodimethylamine precursors through the microbiological metabolism of nitrogenous substrates in water. (15th September 2020) - Bei, Er; Li, Xiao; Wu, Fuhua; Li, Shixiang; He, Xinsheng; Wang, Yufang; Qiu, Yu; Wang, Yu; Wang, Chengkun; Wang, Jun; Zhang, Xiaojian; Chen, Chao
Abstract: N-nitrosodimethylamine (NDMA) as one emerging disinfection by-product has been investigated globally since 1990s. However, its main precursors are still unclear. We found that NDMA formation potential (NDMAFP) of various water samples increased firstly and then decreased gradually during incubation with microorganism. We hypothesized that NDMA precursors could be produced through metabolism of nitrogenous components and then gradually be biodegraded. To verify this hypothesis, six amino acids (AAs), peptone and ammonium were separately incubated with microorganism and NDMAFP was measured regularly. The average molar yield of the substrates to NDMAFP were 60–200 × 10 −6 for the AAs, 350 × 10 −6 for peptone under aerobic condition. The extracellular fraction with molecular weight (MW) less than 1 k Dalton contributed the majority to NDMAFP in the peptone experiment, followed by that with MW between 10 k and 0.22 μm and the intracellular materials. Dimethylamine and methylamine were detected during the experiments but their contribution to NDMAFP is quite limited. The results indicate that the nitrosamine precursors may not be the direct metabolite of AAs or peptones but the excretion of living bacteria or the components in dead bacteria body. Our results inferred that AA metabolism may give an NDMAFP of 0.12 nmol/L (maximum) or 0.09 nmol/L (average) in water under aerobic condition. This estimation of NDMAFP from AA metabolism can account for 38% (maximum) or 27% (average) of the median NDMAFP in waters of China (0.32 nmol/L) reported before. Graphical abstract: Image 1 Highlights: Hypothesis of NDMA precursors formation via microbial metabolism was raised firstly. Hypothesis of NDMA precursors formation via microbial metabolism was verified firstly. Dynamics of NDMA precursors in source waters were observed during incubation. Microbial metabolism of total amino acids contributes NDMA precursor greatly in waters of China.